Necroptosis in vascular cognitive impairment: mechanisms and therapeutic potential - Wei, Shufei; Cheng, Lin; Shen, Chunxiao; Li, Zefen; Teng, Jiahui; Wang, Liangliang; Zhang, Xiaorong (Frontiers in Aging Neuroscience, 2025)
Cerebral ischemia and hypoxia play key roles in the occurrence and development of vascular cognitive impairment (VCI). However, the pathophysiology of VCI remains unclear. Necroptosis is a non-cysteine-dependent form of cell death mediated by serine/threonine kinases receptor-interacting protein kinase-1 and -3 and mixed lineage kinase domain-like protein. A search of PubMed and Web of Science was conducted using terms related to VCI and necroptosis. Necroptosis is important in neuroinflammation, neuronal loss, blood–brain barrier dysfunction, and demyelination. Cerebral ischemia activates the necroptotic pathway, and necroptosis inhibitors have a significant inhibitory effect on brain injury. This review focuses on the pathogenesis of VCI and clarifies the core regulatory mechanism of necroptosis in vascular dementia, which lays a scientific foundation for cognitive impairment prevention and treatment by targeting necroptosis in VCI.